Xenoimplantation of an Extracellular-Matrix-Derived, Biphasic, Cell-Scaffold Construct for Repairing a Large Femoral-Head High-Load-Bearing Osteochondral Defect in a Canine Model. (10th March 2014) - Qiang, Yang; Yanhong, Zhao; Jiang, Peng; Shibi, Lu; Quanyi, Guo; Xinlong, Ma; Qun, Xia; Baoshan, Xu; Bin, Zhao; Aiyuan, Wang; Li, Zhang; Wengjing, Xu; et al.
Abstract : This study was aimed to develop an ECM-derived biphasic scaffold and to investigate its regeneration potential loaded with BM-MSCs in repair of large, high-load-bearing osteochondral defects of the canine femoral head. The scaffolds were fabricated using cartilage and bone ECM as a cartilage and bone layer, respectively. Osteochondral constructs were fabricated using induced BM-MSCs and the scaffold. Osteochondral defects (11 mm diameter × 10 mm depth) were created on femoral heads of canine and treated with the constructs. The repaired tissue was evaluated for gross morphology, radiography, histological, biomechanics at 3 and 6 months after implantation. Radiography revealed that femoral heads slightly collapsed at 3 months and severely collapsed at 6 months. Histology revealed that some defects in femoral heads were repaired, but with fibrous tissue or fibrocartilage, and femoral heads with different degrees of collapse. The bone volume fraction was lower for subchondral bone than normal femoral bone at 3 and 6 months. Rigidity was lower in repaired subchondral bone than normal femoral bone at 6 months. The ECM-derived, biphasic scaffold combined with induced BM-MSCs did not successfully repair large, high-load-bearing osteochondral defects of the canine femoral head. However, the experience can help improve the technique of scaffold fabrication and vascularization.